Investigation on the Binding and Conformational Change of All-trans-Retinoic Acid with Peptidyl Prolyl cis/trans Isomerase Pin1 Using Spectroscopic and Computational Techniques - GuoFei Zhu; ShaoLi Lyu; Yang Liu; Chao Ma; Wang Wang (Journal of Spectroscopy)
Binding and conformational change of all-trans-retinoic acid (ATRA) with peptidyl prolyl cis/trans isomerase Pin1 were investigated systematically by spectroscopic and computational techniques under experimentally optimized physiological conditions. The intrinsic fluorescence of Pin1 was quenched through a static quenching mechanism in the presence of ATRA with binding constants on the order of 105 mol/L. Thermodynamic parameters (ΔH = 15.76 kJ/mol and ΔS = 158.36 J/mol·K at 293 K) and computational results illustrated that the hydrophobic interactions played a significant role in the binding process of ATRA to Pin1, but electrostatic forces, weak van der Waals, and hydrogen bonds cannot be ignored. Circular dichroism, fluorescence spectra, and computational simulations revealed that ATRA interacted with residues Lys63 and Arg69 of Pin1 to affect its conformational changes. Molecular dynamic simulation, principal component analysis, and free energy landscape monitored the dynamical conformational characteristics of ATRA binding to Pin1. All in all, the present research might provide a reference for the development and design of retinoic acid drugs that inhibit the activity of Pin1.